Dynamics of endothelial progenitor cells in patients with advanced hepatocellular carcinoma. Issue 7 (July 2022) - Campani, Claudia; Capone, Manuela; Liotta, Francesco; Arena, Umberto; Adotti, Valentina; Di Bonaventura, Chiara; Aburas, Sami; Colagrande, Stefano; Calistri, Linda; Annunziato, Francesco; Marra, Fabio
Abstract: Background and aims: Circulating endothelial progenitor cells (EPC) predict tumor vascularization and disease progression, but limited information is available on their dynamics in hepatocellular carcinoma (HCC) undergoing systemic treatment. Methods: We prospectively analyzed different populations of EPC in 16 patients with advanced HCC receiving sorafenib. Patients were studied before therapy (T0, n = 16) and after two (T2, n = 12) and eight weeks (T8, n = 8), using high-performance flow-cytometry. The tumor response at T8 was categorized as progressive disease (PD) or clinical benefit (CB, all other responses). Results: At T0, higher levels of CD34 + CD133 + KDR + and CD34 + KDR + were observed in patients with alpha-fetoprotein ≥400 ng/ml or non-viral liver disease, whereas CD34 + CD133 + KDR + cells were virtually absent in patients with vascular invasion. CD34 + KDR + and CD34 + CD133 + KDR + were directly correlated with platelet count. Frequencies of all populations of EPC declined in patients receiving sorafenib. Levels of CD34 + CD133 + were higher at T0 in patients with CB compared to patients with PD. In patients belonging to the CB group CD34 + KDR + cells at T0 were directly correlated to platelet count. Conclusion: In patients with advanced HCC, EPC are directly correlated with platelet count, suggesting a common activation of selected bone marrow pathways. Levels of a CD34 + KDR + are higher at baseline in patients responding to sorafenib.